Neddylation of M1 negatively regulates the replication of influenza A virus. (5th December 2020) - Li, Yucen; Chai, Wenjia; Min, Jie; Ye, Zhen; Tong, Xiaomei; Qi, Dandan; Liu, Wenjun; Luo, Enjie; Li, Jing; Ye, Xin
Abstract : Post-translational modification plays a critical role in viral replication. Previously we reported that neddylation of PB2 of influenza A virus (IAV) can inhibit viral replication. However, we found that NEDD8 overexpression can still inhibit the replication of PB2 K699R mutant viruses, implying that other viral protein(s) can be neddylated. In this study, we revealed that M1 of IAV can also be modified by NEDD8. We found that the E3 ligase HDM2 significantly promotes M1 neddylation. Furthermore, we identified M1 K187 as the major neddylation site. We generated an IAV M1 K187R mutant (WSN-M1 K187R) and compared the growth of wild-type and mutant viruses in Madin–Darby canine kidney (MDCK) cells. The data showed that the replication of WSN-M1 K187R was more efficient than that of wild-type WSN. More importantly, we observed that overexpression of NEDD8 inhibited the replication of the wild-type WSN more effectively than that of WSN-M1 K187R. In addition, we found that the neddylation-deficient M1 mutant (M1 K187R) had a longer half-life than that of wild-type M1, indicating that the neddylation of M1 reduces stability. Then we performed a viral infection assay and found that WSN-M1 K187R exhibited greater virulence in mice than wild-type WSN, suggesting that the neddylation of M1 reduced IAV replication in vivo . In conclusion, we uncovered that neddylation of M1 by HDM2 negatively regulates the stability of M1, which in turn inhibits viral replication.